Strategy for Development of the Domestic Defense Industry to Maintain National Sovereignty and the Integrity of the Unitary State of the Republic of Indonesia in the Era of Revolution 4.0 with the Perspective of National Defense and Defense Science - Novia Rizki Nirwana; I Nengah Putra Apriyanto; George Royke; Aries Sudiarso; Khaerudin (Formosa Journal of Multidisciplinary Research, 2024)
The development of the domestic defense industry plays a key role in maintaining national sovereignty and the integrity of the Unitary State of the Republic of Indonesia in the era of Industrial Revolution 4.0. In this context, complex and dynamic challenges require an integrated approach to strengthen independence in the defense sector. This study highlights the importance of integration between the concept of national defense, defense science and technology in the development of the defense industry. Collaboration between the government, private sector, academic institutions and the military is the key to creating an ecosystem that supports the growth of the domestic defense industry. Greater investment in research and development is needed to produce innovative technologies that can compete globally. Apart from that, regional cooperation is also important in building joint defense capacity and strengthening regional stability. Indonesia needs to establish strategic partnerships with neighboring countries and international partners to support each other in developing the defense industry and maintaining security and peace in the region. By facing challenges with the right solutions, Indonesia has great potential to build an independent and strong domestic defense industry. Through the integration of national defense perspectives, defense science and technology, this country can build a strong national defense foundation and ensure the sovereignty and integrity of the Unitary State of the Republic of Indonesia in this increasingly complex and dynamic era. Thus, this research makes an important contribution to the understanding of the domestic defense industry development strategy and its relevance in the context of national security.